Stress on facial skin of class III subjects during maxillary protraction: a finite element analysis - Francesca Gazzani; Chiara Pavoni; Paola Cozza; Roberta Lione (BMC, 2019)
Abstract Background Maxillary protraction with facemask (FM) is an orthopedic approach for treatment of Class III growing patients. Aim of the present investigation was to analyze tension loads produced by two different facial mask (FM) designs on facial skin of subject with skeletal Class III. Methods A three-dimensional (3D) geometry of Delaire and Petit FM models were reconstructed from the original Computer Aided Design (CAD) 3D prototype using software package (ANSYS 5.7). A traction load of 9.8 N inclined of 30° to the occlusal plane was applied combining analytical FM models with a 3D facial model. Resulting stresses and deformations on the skin layer were tested through the von Mises yield criterion. Results Overall tensions were mostly developed on the chin area, while lower stresses were observed on forehead area for both FM designs. When Delaire FM model was tested, maximum stresses were observed on the upper border of the chin cup corresponding to the inferior lip and to marginal gingiva of lower incisors. After Petit FM application, maximum stresses were more extensively localized at the level of both upper border and central area of the chin. Stresses measured on the chin area were significantly higher with Petit FM when compared with Delaire FM (44 KPa versus 29 KPa, respectively). Conclusions Delaire FM determined lower stresses and tensile tensions than Petit FM model. Highest tensions were observed at the level of chin cup area for both Delaire and Petit FM. Stresses following Delaire FM application were mostly observed on the upper border of the chin cup, while Petit FM determined stresses more extensively distributed to the central area of the chin.